Efektivitas Edukasi Pencegahan Stunting terhadap Peningkatan Pengetahuan Orangtua dalam Upaya Penurunan Risiko Stunting di Desa Sumeith Pasinaro - Ronald Darlly Hukubun; Riskia Tirta Nirwana Sopacua; Jessika Janet Reindah; Agustina Indasari Ngilamele; Gilberto Remse Papilaya; Johan B. Bension (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Stunting is a health issue that remains a concern for the government, particularly in supporting the achievement of the Sustainable Development Goals (SDGs), namely the nutritional status of children under five. Stunting, or chronic malnutrition, causes children to fail to grow, which is influenced by mothers' knowledge of nutritional fulfillment in children, especially from the first 1,000 days of birth until the child is 2 years old. The purpose of this study was to determine the effect of health education on parents in preventing stunting in Sumeith Pasinaro Village. The targets of this study were pregnant and breastfeeding mothers and parents who had children aged 1-5 years. This study used a One Group Pre-test-Post-test design with paired sample t-test analysis. There were 12 participants in the activity. Data were collected through a multiple-choice questionnaire administered before and after the socialization with the material “Prevent Stunting from the Heart.” The average pre-test score of the participants was 6.75 and then increased to 9.33 on the post-test, with a difference of 2.58. The paired sample t-test results showed a Sig. (2-tailed) value of 0.014 (< 0.05), indicating a significant increase in participants' knowledge after receiving education. Therefore, health education through socialization activities is effective in increasing mothers' knowledge about stunting prevention. Activities like this are important to continue as an effort to reduce the incidence of stunting in the community.